Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.5 Higher Derivatives - Exercises: 10

Answer

$y' = -15t^{-4}-\dfrac{56}{3}x^{-11/3}$ $y'' = 60t^{-5}+\dfrac{616}{9}x^{-11/3}$ $y''' = -300^{-6}-\dfrac{8624}{27}x^{-17/3}$

Work Step by Step

$y' = -15t^{-4}-\dfrac{56}{3}x^{-11/3}$ $y'' = 60t^{-5}+\dfrac{616}{9}x^{-11/3}$ $y''' = -300^{-6}-\dfrac{8624}{27}x^{-17/3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.